Firm Size and Environmental Disclosure Among Firmlisted on the Nairobi Securities Exchange (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the relationship between firm size and environmental disclosure among firms listed on the Nairobi Securities Exchange (NSE). Environmental disclosure has become an important aspect of corporate accountability due to increasing global concerns regarding environmental sustainability. However, environmental reporting among Kenyan firms remains largely voluntary because of limited regulatory frameworks and absence of mandatory disclosure standards. The study adopted an explanatory research design and utilized secondary data collected from annual reports of firms listed on the NSE for the period 2018–2022. Content analysis was employed to extract environmental disclosure information, while descriptive and inferential statistics were used to analyze the data. Environmental disclosure was measured using an environmental disclosure index developed from a disclosure checklist. Firm size was measured using the logarithm of total annual sales turnover. Regression analysis findings revealed that firm size had a positive and significant relationship with environmental disclosure (β = 0.147, p = 0.010). Pearson correlation results also confirmed a significant association between firm size and environmental disclosure (r = 0.217, p = 0.001). The study concludes that larger firms are more likely to disclose environmental information than smaller firms due to increased public visibility and stakeholder pressure. The study recommends the establishment of mandatory environmental disclosure guidelines to improve transparency and sustainability reporting among listed firms in Kenya.